Influence of Changes in the Prices of Fertilizers and Fuels on the Profitability of Production of Selected Agricultural Crops - Arkadiusz Weremczuk; Grzegorz Militka (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The prices of raw materials necessary for production play an important role in the production decisions of farmers, and thus in shaping the level of supply of agricultural raw materials. The constant increase in the prices of raw materials for production increases its costs. Therefore, it should be noted that the rising prices of fuel and fertilizers affect the decisions and profitability of plant production. In connection with the above, this study attempts to indicate the impact of changes in fertilizer and fuel prices on the profitability of production of selected agricultural crops in Poland. The paper uses secondary data on the price level of fertilizers, fuels and selected agricultural products, as well as the structure of their production costs. Based on the sensitivity analysis, the potential impact of the increase in fuel and fertilizer prices on the profitability of the production of selected species was indicated. The results showed that the increase in the prices of the above-mentioned raw materials can significantly affect the economic efficiency of the production activity.